2017
DOI: 10.1021/jacs.7b04865
|View full text |Cite
|
Sign up to set email alerts
|

PdSe2: Pentagonal Two-Dimensional Layers with High Air Stability for Electronics

Abstract: Most studied two-dimensional (2D) materials exhibit isotropic behavior due to high lattice symmetry; however, lower-symmetry 2D materials such as phosphorene and other elemental 2D materials exhibit very interesting anisotropic properties. In this work, we report the atomic structure, electronic properties, and vibrational modes of few-layered PdSe exfoliated from bulk crystals, a pentagonal 2D layered noble transition metal dichalcogenide with a puckered morphology that is air-stable. Micro-absorption optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
761
2
12

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 594 publications
(861 citation statements)
references
References 37 publications
53
761
2
12
Order By: Relevance
“…Moreover, we are also able to observe a shift in the lowest point of CBM from S point to in-between S and Y points, and highest point of VBM from near Γ region to in-between Γ and X, during the transition from 1L to 2L. For comparison with experimental studies [12,19,35], the calculated band gaps (table S1) of the corresponding pyrite thin film structures are relatively in good agreement with experimental findings. Figure 4(b) shows the calculated band structures of 1T PdSe 2 from 1L to 5L thickness.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, we are also able to observe a shift in the lowest point of CBM from S point to in-between S and Y points, and highest point of VBM from near Γ region to in-between Γ and X, during the transition from 1L to 2L. For comparison with experimental studies [12,19,35], the calculated band gaps (table S1) of the corresponding pyrite thin film structures are relatively in good agreement with experimental findings. Figure 4(b) shows the calculated band structures of 1T PdSe 2 from 1L to 5L thickness.…”
Section: Resultssupporting
confidence: 83%
“…1T, 2H, and 3R [11]. Moreover, recent studies [12][13][14][15][16][17][18][19][20] have shown that some TMDs can also exhibit orthorhombic structures, specifically pyrite and marcasite structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20] Among them, palladium diselenide (PdSe 2 ) is attracting attention due to its interesting electronic properties and atomic structure. [24,25] In contrast to the frequently reported hexagonal phases in TMDs, PdSe 2 has a unique structure, Figure 1a. [24,25] In contrast to the frequently reported hexagonal phases in TMDs, PdSe 2 has a unique structure, Figure 1a.…”
Section: Doi: 101002/adma201904251mentioning
confidence: 82%